2008
DOI: 10.1017/s0014479708006339
|View full text |Cite
|
Sign up to set email alerts
|

CROP DEVELOPMENT AND ROOT DISTRIBUTION IN LESSER YAM (DIOSCOREA ESCULENTA): IMPLICATIONS FOR FERTILIZATION

Abstract: A growth analysis study involving monthly excavation of Dioscorea esculenta plants revealed that the root system developed fully in the period before tuber initiation, and extended radially for a distance between 2.3 and 4.3 m. Primary roots initially remained in the top 10 cm of the soil profile, but descended to approximately 30 cm near their full extension. Tuber number increased from initiation around 21 weeks after planting (WAP) until maximum vine growth was reached around 33 WAP, but tuber dry weight co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
12
2
1
Order By: Relevance
“…Finally, it is worth noting that unfertilized plants had not taken up any of the 15 N added in the nearby fertilized plot. This suggests that the maximum length of the roots of our cultivar of D. alata was <3 m and therefore smaller than the maximum root length reported by O'Sullivan (2008) and Melteras et al (2008), who observed roots of D. alata and D. esculenta foraging at 4 m and more from the plant while their yams had been planted in 15‐ and 50‐cm mounds, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…Finally, it is worth noting that unfertilized plants had not taken up any of the 15 N added in the nearby fertilized plot. This suggests that the maximum length of the roots of our cultivar of D. alata was <3 m and therefore smaller than the maximum root length reported by O'Sullivan (2008) and Melteras et al (2008), who observed roots of D. alata and D. esculenta foraging at 4 m and more from the plant while their yams had been planted in 15‐ and 50‐cm mounds, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…The maximum RLD of 0.26 cm cm (3 observed in D. rotundata was smaller than the maximum RLD of 11.3 and 1.5 cm cm (3 , reported for potatoes (Ahmadi et al 2011) and cassava (Lose et al 2003), respectively. The root spatial distribution pattern observed in this study showed that D. rotundata is also a shallow-rooting species, similar to D. esculenta (Melteras et al 2008), D. alata (Hgaza et al 2011), cassava (Lose et al 2003) and potatoes Groenwold 1986, Ahmadi et al 2011).…”
Section: Discussionsupporting
confidence: 62%
“…Only one reference was found for yams, the second most important root crop in Sub-Saharan Africa 1 , which described two distinct well-organized root systems: the seminal root system and the adventitious, more definitive root system (Charles-Dominique et al, 2009). Other studies in yam only focused on root morphology at crop harvest stage in response to fertilization (Melteras et al, 2008; O’Sullivan, 2008; Hgaza et al, 2012). Iwama et al (1977) specifically analyzed root systems and the relationship between root systems and tuber yield in potato (Iwama et al, 1981).…”
Section: Root System Architecture In Root and Tuber Cropsmentioning
confidence: 99%